Adiwiyata-Based School Management in Indonesia - Mahendrartha, Azizul; Tobari, Tobari; Tabula, Rommel Valencia (Journal of Social Work and Science Education, 2020)
This study was to determine Adiwiyata-Based School Management in SMP Negeri 5 Prabumulih. Data were collected using observation, documentation, and interviews. While the method used is descriptive qualitative method. The results of the research indicate that (1) the implementation of the Adiwiyata Program has successfully contained a vision, mission, goals and targets which include environmental protection and management policies, (2) The Adiwiyata School Program has included the 2013 Curriculum which is carried out thematically and integrated with all environmental-based subjects, (3) participatory-based environmental activities in the Adiwiyata Program have been carried out well by all school residents in order to maintain and maintain the school building and environment, (4) the school has managed well supporting facilities that are environmentally friendly and child-friendly. The headmaster of Prabumulih 5 Middle School in the Adiwiyata School Program has been running successfully, as evidenced by the award as the 2019 Adiwiyata National School from the Ministry of the Environment.